Effects of added caper on some physicochemical properties of White Cheese - Oktay Yerlikaya; Cem Karagozlu (Mljekarstvo)
In this study, the effects of caper berries addition on some physicochemical and functional properties of White Cheese were investigated. Three batches of White Cheese were produced: a control group with no caper addition (C), a group with whole grain caper addition (W) and a group with minced caper addition (M). Caper berries were added to the cheese vat after cutting at a level of 8 g per 100 g of curd weight. Changes in chemical compositions, proteolysis (ripening index), lipolysis (acid degree value), free amino acids, free fatty acids (FFAs), and some mineral substances of White Cheese samples were analysed during the ripening period for 90 days at +4 °C. According to the results obtained from statistical analyses, when compared to control sample, there was a significant difference by adding caper to White Cheese for salt %, lactic acid %, and mineral contents (p<0.05). Generally, the data obtained from this study showed that adding caper to White Cheese reduced some quality characteristics, while some properties such as physicochemical were improved